Khaki-tinted glasses: Nostalgia and memory at wartime in TV's M*A*S*H. Issue 1 (1st March 2020) - Hall, Martin
This article looks at the fruitful and well-loved television show M*A*S*H (1972‐83) through the lens of postmodernism and explores the extent to which nostalgia plays a role in meaning making. M*A*S*H, which was made predominantly in the 1970s, was set in the 1950s and refers quite explicitly to the 1960s, inherently uses 'memory' as a vehicle for delivering the show's messages. By analysing the presence of material artefacts such as letters and food, this article demonstrates the prolificacy of the show's overwhelmingly nostalgic approach to analysing American society across several decades.